The dislocation resonance absorption of ultrasoundin KBr crystals at low temperatures - Petchenko, G.A.; Petchenko, A.M. (Functional Materials, 2009)
The frequency spectra of ultrasound dislocation losses in KBr single crystals with different dislocations density Λ have been researched at fixed temperatures in the T = 300-77 K interval. It is found that at any T = const within the mentioned range, the inversion effect is observed resulting from the sample deformation. The effect has been discussed in the framework of the dislocation interaction model. The viscosity coefficient B has been established to be independent of Λ within the whole temperature range. The experimental data on B(Λ) have been found to agree with the conclusions from the Alshits-Indenbom theory of dynamic dislocation drag.